A quarter-circled multi-resonator for UWB re-transmission based chipless RFID - Wan Mohamed, Ghazi; Hossain, A K M Zakir; Abd. Aziz, Mohamad Zoinol Abidin; Azam, S. M. K. (2023)
This paper introduces the design and analyses of a new planar parallel microstrip quarter-circled multi-resonator (PQMR) for the chipless radio frequency identification (CRFID) that works in ultra-wide band (UWB) frequency region. The proposed PQMR has identifying (IDing) and potential sensing capabilities to work as a tag-sensor. The PQMR works within 3.30 GHz – 6.53 GHz with a high -10dB quality-factor (Q10dB) of 692, a good spatial density of as low as 7.05 mm2